Two local extremes of cutting speed - Macurova, Anna; Vasilko, Karol (Manufacturing Technology Journal, 2012)
In 1906 Taylor mathematically defined the dependance of tool durability on cutting speed in the form: T=CT/vm for the first time. It is an equation of a hyperbola, which represents itself as a straight line in double logarithmic net according to Taylor. The dependance is valid for the tools made of high-speed steel. It has still been used in spite of the fact that new cutting materials, which cannot be used according to it, or can be used only partially in a narrow range of higher cutting speeds. The course of function T=f(vc) for the tools made of sintered carbid and ceramics will be identified in the paper. It requires extensive durability tests in a wide range of cutting speed. Interesting conclusions can be derived from its course.
Keywords: surface roughness; cutting force; tool life